2005
DOI: 10.1016/j.polymer.2005.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior of polymer/montmorillonite nanocomposites. Part I. Intercalated poly(ethylene oxide)/montmorillonite nanocomposites

Abstract: The influence of montmorillonite (MMT) silicate layers on the semicrystalline morphology development of the poly(ethylene oxide) (PEO) matrix of PEO/MMT nanocomposites has been investigated by using X-ray diffraction, differential scanning calorimetry, light microscopy and time-resolved simultaneous small-and wide-angle X-ray scattering. The silicate layers act as nucleating agents for the crystallization of PEO, but at high contents also have a retarding effect on the crystal growth. In that case they are non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
58
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 28 publications
9
58
0
1
Order By: Relevance
“…These results are an indirect indication that the MMT clay might be concentrated in the GBL phase instead of the polymer phase for high loading of clay. A similar behavior was observed by Homminga et al 36 for electrolytes prepared with PEO and MMT. At low concentrations of clay, these inorganic particles interact randomly with the polymer.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…These results are an indirect indication that the MMT clay might be concentrated in the GBL phase instead of the polymer phase for high loading of clay. A similar behavior was observed by Homminga et al 36 for electrolytes prepared with PEO and MMT. At low concentrations of clay, these inorganic particles interact randomly with the polymer.…”
supporting
confidence: 87%
“…For the sample containing 3% of clay, the inorganic additive induces a small crystallization at -10 o C followed by a melting at ca. 16 o C. For the pure polymer sample such crystallization is seen at -31 o C. 38 Homminga et al 36 observed a similar effect in their system where MMT retards the PEO crystallization at low clay content. Here, the presence of clay shifts the crystallization to higher temperatures.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…181 Do sličnih zaključaka se došlo u ispitivanju uticaja čestica gline na brzinu kristalizacije poli(etilen oksida), ali u ovom slučaju udeo punila nema uticaja na stepen kristaliničnosti i stukturu i morfologiju nastalih kristalita. 182 U slučaju nanokompozita poli(laktida) i organski modifikovane gline ukupna brzina kristalizacije polimera je veća u nanokompozitu nego u čistom poli(laktidu), jer čestice gline predstavljaju dodatne nukleuse za kristalizaciju poli(laktida). Tu nastaje veći broj sferulita manjeg prečnika nego pri kristalizaciji samog poli(laktida), ali čestice gline nemaju uticaja na linearnu brzinu rasta samih sferulita.…”
Section: Svojstva Polimernih Nanokompozitaunclassified